Polymer-like double necking deformation in an FeCoCrV medium entropy alloy - Si Gao; Yao Xiao; Jiankun Liu; Reza Gholizadeh; Myeong-Heom Park; Shuhei Yoshida; Wenqi Mao; Yanzhong Tian; Nobuhiro Tsuji (Materials Research Letters)
Necking in metallic materials is a crucial strain localization phenomenon traditionally regarded as the termination of uniform deformation and the sign of impending fracture. Here, we report an FeCoCrV medium entropy alloy (MEA) can exhibit two successive necking events during tensile deformation — a double necking behavior previously believed to occur only in polymer materials — thereby challenging the conventional understanding of necking in metals. We clarified the first neck in our MEA is stabilized by post-necking strengthening through deformation induced martensitic transformation, allowing for it to propagate to un-necked region instead of further localizing.